ORGANIZATION ETHICS REPUTATION AND CUSTOMER LOYALTY: Perception of Muslim Customer Sharia Banking - Sunaryo SUNARYO; Zakaria Bahari (APMBA (Asia Pacific Management and Business Application), 2012)
The majority of the Indonesian population is Muslim, in which the share of Sharia Banking is only three (3) percent of the total banking market share in the country. This indicates a low participation, possibly leading to a negative perception on ethic reputation and low awareness among the Muslim communities in using sharia banking products and services. The objectives of this paper are to analyze the influence of sharia banking organization ethics reputation on Muslims customer loyalty and to analyze the role of satisfaction as a mediating effect on sharia banking organization ethics reputation on Muslims customer loyalty for the sharia banking products and services. Survey with 315 respondents in the city of Malang, Indonesia was conducted to gather information to further understand the situation, to answer the questions raised and to meet the study objectives. Purposive sampling was used to select the relevant respondents. The Structural Equation Model (SEM) is used to analyze the direct and indirect relationship between sharia banking organization ethic reputation, satisfaction and Muslims customer loyalty. The findings of this study showed that all independent variables significantly influenced the dependent variable, both directly and indirectly. Satisfaction as mediating factor has a high positive support to the relationship between organization ethic reputation Muslims customer loyalty. Hence, satisfaction plays an important role to support the perception of ethic reputation of the sharia banking organization in influencing Muslim customer loyalty. In addition, the study also suggests that ethic reputation of an organization also helps in maintaining customer loyalty.